Взаємозв’язок правосвідомості і моралі в діяльності працівників поліції України як чинник протидії професійній деформації - Швець, Д. В.; Shvets, D. V.; ORCID: http://orcid.org/0000-0002-1999-9956; ResearcherID: B-9071-2018 (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2018. – № 1. – С. 16-22, 2018)
Здійснено аналіз поняття професійної деформації. З’ясовано основні причини виникнення професійної деформації поліцейських в Україні. Розглянуто взаємозв’язок і роль правосвідомості та моралі у професійній діяльності працівників поліції.

It can’t be said that nowadays the overwhelming majority of policemen in Ukraine are principal, honest, fair and impartial people. Such personal qualities are results of professional deformation. Professional deformation of policemen is a negative change of policemen’s moral and psychological strains, their relations with colleagues and society in their professional activity. Moreover, professional police duties, communication with different people, lack o f free time and psychological training, bad attitude to the police work and emotional tension are the main reasons of policemen’s professional deformation. Irritability, decrease of professional activity, sense of fear and despair, hopelessness, lack of initiative will be the consequences of professional deformation. Professional sense of justice and morality play an important role in overcoming of police officer’s professional deformation. Morality is an objective phenomenon, based on experience and knowledge, which forms feelings and comes from motivation, faith and dominance of good. Legal consciousness consists of thoughts, views, feelings, which express an understanding of necessity establishing and operating of certain law order in society. Legal consciousness and morality are not the same categories and are the forms of social consciousness, but there is a quite close connection between them. In addition, it can be said that these both categories play an important role in overcoming of professional deformation.. In conclusion of the article, the author says that the increasing level of professional sense of justice and law culture, development of moral qualities, formation of good psychological climate between colleagues among police officers, equal attitude to different people despite of their special features, selfdevelopment, attention, self-control and awareness of importance and responsibility of their work are the most important ways of overcoming and prevention of police officers professional deformation.

Осуществлен анализ понятия профессиональной деформации. Выяснены основные причины возникновения профессиональной деформации полицейских в Украине. Рассмотрена взаимосвязь и роль правосознания и морали в профессиональной деятельности сотрудников полиции.
Interconnection between legal consciousness and morality in police work in Ukraine as an element of professional deformation’s counteraction
Швець Д. В. Взаємозв’язок правосвідомості і моралі в діяльності працівників поліції України як чинник протидії професійній деформації / Швець Д. В. // Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2018. – № 1. – С. 16-22.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; професійна деформація; правосвідомість; мораль; поліцейський; профессиональная деформация; правосознание; полицейский; professional deformation; legal consciousness; morality; police officers